Disturbed testicular expression of the estrogen‐metabolizing enzymes CYP1A1 and COMT in infertile men with primary spermatogenic failure: possible negative implications on Sertoli cells. (23rd March 2017) - Parada‐Bustamante, A.; Molina, C.; Valencia, C.; Flórez, M.; Lardone, M. C.; Argandoña, F.; Piottante, A.; Ebensperguer, M.; Orihuela, P. A.; Castro, A.
Summary: Estradiol (E2 ) is normally metabolized to hydroxyestradiols and methoxyestradiols by CYP1A1, CYP1B1 and COMT. However, an altered production of these metabolites by a disturbed expression of these enzymes is associated with reproductive and non‐reproductive pathologies. In vitro studies suggest that increased hydroxyestradiols and methoxyestradiols intratesticular generation is related to male infertility, but no studies have explored whether infertile men have a disturbed testicular expression of the enzymes that generate these E2 metabolites. The aim of this study was to assess CYP1A1, CYP1B1 and COMT testicular expression at mRNA and protein level in men with spermatogenic impairment. Seventeen men with primary spermatogenic failure (13 with Sertoli cell‐only syndrome and four with maturation arrest) and nine controls with normal spermatogenesis were subjected to testicular biopsy. mRNA was quantified using real‐time RT‐PCR and protein expression was evaluated using western blot and immunohistochemistry followed by integrated optic density analysis. Besides, the effects of hydroxyestradiols and methoxyestradiols on testosterone‐induced transcriptional activity were evaluated in TM4 cells using a luciferase reporter assay system. Our results show that patients with Sertoli cell‐only syndrome had significantly elevated COMT expression at the mRNA level, higher COMT immunoreactivity in their seminiferous tubules and increased protein expression of the soluble COMT isoform (S‐COMT), whereas patients with maturation arrest had significantly elevated CYP1A1 mRNA levels and higher CYP1A1 immunoreactivity in interstitial space. Finally, 2‐hydroxyestradiol decreased testosterone‐induced transcriptional activity in Sertoli cells in vitro. In conclusion, male infertility is related to disturbed testicular expression of the enzymes responsible for producing hydroxyestradiols and/or methoxyestradiols. If these changes are related with increased intratesticular hydroxyestradiols and methoxyestradiols concentrations, they could elicit an impaired Sertoli cell function. Our results suggest CYP1A1 and COMT as new potential targets in treating male infertility.